Kehidupan Keberagamaan Masyarakat Talang di Propinsi Jambi - SM, Muntholib (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This article aims at observing Masyarakat Talangs (talang-society) religious experience in their very life focusing on the basic of the their relationship patterns. By employing descriptive approach, this article finds that their religious (Islamic) education begins in the early stage in household, but for the adults, they have religious education and experiences by activating some religious bodies like Yasinan (reciting some of the holy Qur an verses together), lembaga Imam (leadership council), Khatib (the preachers) and bilal (summoners). All activities are conducted alternately in different houses at the prescribed time. For the vertical relationship to their creator, they do the religious ritual.